Natural lighting of road pre-tunnels: A methodology to assess the luminance on the pavement – Part I. (March 2018) - Cantisani, Giuseppe; D'Andrea, Antonio; Moretti, Laura
Abstract: This two-part paper presents a comprehensive methodology for lighting calculation of a road pre-tunnel. The adequate lighting of road tunnels, especially in their entrance zone during the day-time hours, is a very important factor to maintain road safety and to ensure a good level of service. These targets are commonly achieved by means of artificial lighting systems. In some cases, nevertheless, it could be preferable to build a pre-tunnel, which reduce and control the natural lighting contribution, in the threshold zone of the tunnel. The structure, in fact, filters the natural light and permits to achieve the required luminance levels on the road pavement, so ensuring the correct visibility to the drivers. The authors expose the theoretical principles and the analysis criteria to control lighting levels in a pre-tunnel lighting (PTL), under various external environmental conditions. The objective of the first part of the paper is to present original analytical models developed by the authors to represent the luminance of clear not terse sky and to assess the illuminance underneath a PTL. The proposed equations permit to compute the sky and PTL contributions considering both direct and reflective radiations, under specific conditions of the examined tunnel (e.g. geometry and materials of PTL, latitude of the site, alignment of the road, etc.). The models and the proposed methodology were also validated by means of an experimental activity, which will be illustrated in the second part of the paper.